Autonomic and Trusted Computing 6th International Conference, ATC 2009 Brisbane, Australia, July 7-9, 2009 Proceedings - González Nieto, Juan; Wang, Guojun; Reif, Wolfgang; Indulska, Jadwiga (Programming and Software Engineering, 2009)
This book constitutes the refereed procedings of the 6th International Conference on Autonomic and Trusted Computing, ATC 2009, held in Brisbane, Australia, in July 2009, co-located with UIC 2009, the 6th International Conference on Ubiquitous Intelligence and Computing. The 17 revised full papers presented together with one invited paper and one keynote talk were carefully reviewed and selected from 52 submissions. The regular papers are organized in topical sections on organic and autonomic computing, trusted computing, wireless sensor networks, and trust.